Regulatory Tools, Effective Markets, and Private Sector Participation in the Forestry and Wood Products Processing Sectors : Issues and Solutions for Developing Countries - World Bank (World Bank, Washington, DC, 2019)
This report presents a framework for strengthening the effectiveness and efficiency of regulation of forestry and related sectors. It strives to identify and reduce regulatory burdens on private firms active in the forestry sector, while not compromising the objectives of government regulation. Illegal logging and deforestation, especially in developing countries, has significant impact on national and global forestry product markets, leading to increasingly heavy regulation of forestry sectors-including downstream markets and processing industries. Heavy regulation places a disproportionate burden on SMEs and frequently leads to regulatory failures, including corruption and reduced competition. As a result, many small-scale forestry and downstream private firms cannot comply with regulatory requirements, and instead operate informally. Reduced regulatory compliance leads to a failure to achieve intended and important social, economic, and environmental outcomes. The report is the first to assess the forestry sector from a cross-cutting global regulatory governance perspective. It draws upon and synthesizes key thematic issues and lessons from available materials on forestry, and develops practical solutions based on problem-driven adaption and good practices documented in regulatory governance literature. Based on this, it also creates a framework and toolkit using a selected and appropriate regulatory governance reform tools for application and further development.